Influence of stochastic volatility for option pricing - Akvilina Valaitytė; Eimutis Valakevičius (Lietuvos Matematikos Rinkinys)
The article analyzes three models of stochastic volatility. Investigation of influence of stochastic volatility for pricing options traded in the Vilnius bank is done.